Revision of the genus Charippus Thorell, 1895, with descriptions of eight new species (Araneae, Salticidae, Euophryini) - Yu, Kun; Wang, Weihang; Maddison, Wayne P.; Zhang, Junxia (Zootaxa, 2022)
The euophryine genus Charippus Thorell, 1895 is revised and eight new species are described: Charippus asper Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. bukittimah Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. callainus Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. denjii Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. heishiding Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. kubah Yu, Maddison & Zhang, sp. nov. (♂ ♀), C. minotaurus Yu, Maddison & Zhang, sp. nov. (♂ ♀) and C. wanlessi Yu, Maddison & Zhang, sp. nov. (♂ ♀). A new combination for Charippus yunnanensis (Cao & Li, 2016) comb. nov. (ex. Cytaea Keyserling, 1882) is proposed, and its female is described for the first time. Diagnostic illustrations and photographs are provided for all known species.